Scitovsky, behavioural economics, and beyond - Maurizio Pugno (Kiel Institute for the World Economy (IfW), 2013)
By revisiting Scitovsky's work on well-being, which introduces 'novelty' into the consumer's option set as a peculiar source of satisfaction, this paper finds a number of connections with the recent behavioural economics so as to open new lines on inquiry. First, similarly to behavioural economics, Scitovsky used psychology to interpret sub-optimal choices. However, his welfare benchmark is different from rational choice, as understood by the economists, because 'novelty' implies a very strong form of uncertainty, as well as learning. Second, Scitovsky contributed to further elaboration of the two-systems framework put forward by Kahneman's recent book, which attempts to base behavioural economics on new foundations. Third, Scitovsky anticipated and contributed to specific analytical issues that have been studied in behavioural economics, such as the role of people's skill in uncertainty, the unpredictability of taste changes, and harmful addiction.
Keywords: B31; D03; D11; 330; Scitovsky; behavioural economics; novelty; consumption skill; strong uncertainty; harmful addiction